Quantifying CO2-H2S interaction in near-wellbore environments: A geochemical perspective - Ahmad Amirhilmi A Razak; Ismail M. Saaid; Muhammad Aslam Md yusoff; M.Fakrumie Zaidin; Farhana Jaafar Azuddin; Sahriza Salwani Md Shah; Norshida Mohsin; Sharidah M. Amin; Yong Wen Pin; Wan Mohd Shaharizuan Mat Latif (Journal of Hunan University, 2024)
This paper presents the findings of experiments conducted to study the geochemistry of carbon dioxide (CO2) and hydrogen sulfide (H2S) in near-wellbore environments during geological carbon sequestration (GCS). The interactions of CO2 and H2S with carbonate rock can result in carbonation, sulfidation, acidification, and mineral precipitation reactions. These chemical reactions can lead to the dissolution of carbonate rock, release of calcium or magnesium ions, formation of sulfides, and precipitation of minerals such as sulfates and carbonates. These complex reactions have significant implications for the properties and integrity of the rock, especially in the context of CO2 or natural gas storage with impurities like H2S, affecting the long-term stability and containment of these fluids. The results indicate that the aging process had limited effects on the porosity and permeability of the carbonate samples, except for the condition with 250-ppm H2S concentration. X-ray diffraction (XRD) analysis revealed that the dominant mineral composition remained relatively unchanged, while the presence of H2S promoted the formation or retention of clay minerals. Computed topography (CT) scan analysis showed varying effects on the average CT value, with higher H2S concentrations resulting in more pronounced changes, indicating greater reaction or alteration. Inductively coupled plasma (ICP) analysis demonstrated the release of cations and anions, dissolution of minerals, production of bicarbonate, calcite, and magnesium, and reduction in sulfate ions. These findings provide valuable insights into the behavior and stability of carbonate rocks in near-wellbore environments under CO2-H2S interactions. Understanding these complex geochemical processes is crucial for assessing the long-term stability and containment of CO2 or natural gas with impurities like H2S in geological storage scenarios.